24 Peak circumferential strain assessed using strain-encoded cardiac magnetic resonance (dense) in healthy volunteers at 1.5- and 3.0 TESLA. (26th April 2015) - Mangion, Kenneth; Clerfond, Guillaume; Carrick, David; McClure, John; Rauhalammi, Samuli M; Corcoran, David; McComb, Christie; Radjenovic, Aleksandra; Berry, Colin
Abstract : Background: Displacement Encoding with Stimulated Echoes (DENSE) is a strain-encoded cardiac magnetic resonance (CMR) method that directly quantifies left ventricular (LV) mechanics within myocardial regions. Strain values might vary according to CMR field strength. In order to assess this possibility, we implemented strain-encoded CMR at 1.5 Tesla and 3.0 Tesla with DENSE in healthy adults. Methods: Healthy volunteers without any medical history or treatment gave informed consent and underwent CMR at 1.5T (Magnetom Avanto, Siemens Healthcare) and 3.0T (Magnetom Verio; Siemens Healthcare) within 24 h. The imaging protocol included balanced steady state free precession (b-SSFP) sequences for cardiac anatomy and function and strain-encoded CMR with DENSE. (CIM_DENSE2D software (University of Auckland, New Zealand; Siemens Healthcare). Global- and segmental circumferential strain was measured at the mid-ventricular level. Results: Sixty five participants (31 (48%) male, mean age 44 ± 18) were included (Table 1). Mean global and regional strain values differed slightly between 1.5T and 3.0T, and these differences were mainly related to strain values in the anterior and anterolateral LV segments were LV displacement is greatest. Conclusion: Strain-encoded CMR with DENSE provides regionally localised measurements of circumferential strain. Subtle field-strength differences were apparent for anterior/antero-lateral LV strain. Funding: Medical Research Scotland project grant. Professor Berry was supported by a Senior Clinical Fellowship from the Scottish Funding Council.